Selective H2PO4− anion sensing by two neutral Zn2+ complexes and combined theoretical and experimental studies of their structural and spectral properties. (8th January 2015) - Hens, Amar; Mondal, Pallab; Rajak, Kajal Krishna
Abstract : Graphical abstract: Two mononuclear Zn 2+ complexes containing O, N, N coordinating ligands derived from thiazole and a substituted phenol moiety have been synthesized. The X-ray structure of one complex is reported as a representative case. The mechanism of metal ion interaction with the ligands has been confirmed by emission and absorbance titrations. The sensing properties of the synthesized complexes towards the phosphate ion are studied. Full density functional theory (DFT) and time-dependent density functional theory (TDDFT) have been investigated to get a better insight into the geometry, electronic structure and optical properties of this system. Abstract: The reactions of azo-phenol based receptors (HL) having an azo core incorporated with thiazole and substituted phenol moieties with Zn 2+ in a 1:2 (M:HL) molar proportion in methanol at ambient condition afforded complexes of the composition [Zn(L)2 ] in excellent yields. Here L is the deprotonated form of 2-(2-thiazolylazo)-p-cresol (HL 1 ) and 4-(2-thiazolylazo)-resorcinol (HL 2 ). Their detailed optical properties have been investigated experimentally and theoretically. The mechanism of the metal–ligand interaction has been established by absorption and emission spectroscopic experiments, which corroborate the favorable coordination of the Zn 2+ ion to the ligand moiety, leading to the formation of two five-membered chelating rings with 1:2 (M:L) complexes. Both of the complexes display a remarkable selectivity towards a decreasing fluorescence intensity nature with an increasing concentration of the H2 PO4 − (Pi) anion in aqueous-acetone (4:1 v/v) buffer solution (pH 7.4, 0.01 M HEPES) at room temperature. DFT and TDDFT calculations reveal that the ICT process takes place from the p-cresol ring (donor, HOMO) to thiazole and azo moiety (acceptor, LUMO) with the enhancement of fluorescence intensity via a CHEF mechanism during complexation between Zn 2+ and the ligand.